2015
DOI: 10.1002/2015gl064195
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic ice rise formation, evolution, and stability

Abstract: Antarctic ice rises originate from the contact between ice shelves and one of the numerous topographic highs emerging from the edge of the continental shelf. While investigations of the Raymond effect indicate their millennial‐scale stability, little is known about their formation and their role in ice shelf stability. Here we present for the first time the simulation of an ice rise using the BISICLES model. The numerical results successfully reproduce several field‐observable features, such as the substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…Embedded into an ice shelf, an ice rise creates a zone of compression upstream of the ice rise that buttresses the ice shelf (Borstad et al, 2013). However, downstream of the ice rise the tensile forces leave a weak region subject to crevasses and thinner ice shelves (Favier and Pattyn, 2015). Also, ice rises strongly influence regional surface mass balance (SMB) (Lenaerts et al, 2014) and can significantly alter the timing of deglaciation of the ice sheet (Favier and Pattyn, 2015;Favier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embedded into an ice shelf, an ice rise creates a zone of compression upstream of the ice rise that buttresses the ice shelf (Borstad et al, 2013). However, downstream of the ice rise the tensile forces leave a weak region subject to crevasses and thinner ice shelves (Favier and Pattyn, 2015). Also, ice rises strongly influence regional surface mass balance (SMB) (Lenaerts et al, 2014) and can significantly alter the timing of deglaciation of the ice sheet (Favier and Pattyn, 2015;Favier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, downstream of the ice rise the tensile forces leave a weak region subject to crevasses and thinner ice shelves (Favier and Pattyn, 2015). Also, ice rises strongly influence regional surface mass balance (SMB) (Lenaerts et al, 2014) and can significantly alter the timing of deglaciation of the ice sheet (Favier and Pattyn, 2015;Favier et al, 2016). Hence, although relatively small in areal footprint, ice rises can have far-reaching effects on Antarctic ice-sheet dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Because ice rises decelerate ice flowing from the continent towards the ocean, they play an important role in defining the dynamics of the sheet-shelf system. Favier and Pattyn (2015), for example, showed that ice rises significantly delay grounding-line retreat during deglaciation and hence impact the timing of sea level changes. In order to better understand the deglaciation history and inevitably also ice-sheet dynamics in the future, there is high interest in collecting observational data that testify to ice-rise evolution (Matsuoka and others, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because ice rises (Goldberg and others, 2009;Favier and others, 2014;Favier and Pattyn, 2015) and ice rumples (Favier and others, 2012) affect the dynamics of the grounding line and that of the upstream catchment area, it is important to better understand what role these features play in defining the buttressing strength of ice shelves.…”
Section: Introductionmentioning
confidence: 99%